Management of Character Education Through Habituation at SMA Muhammadiyah Darul Arqom Karanganyar in 2021 - Dwi Sugeng Riyadi; Harun Joko Prayitno; Bambang Sumardjoko (CV. Rayyan Dwi Bharata, 2022)
This study aims to determine the management of character education through habituation at Muhammadiyah Darul Arqom Karanganyar High School in 2021. This research is a qualitative research Research design using phenomenological design or design. The research was carried out at Muhammadiyah Darul Arqom Karanganyar High School which was addressed at Tegalasri RT 05 RW VI, Bejen, Karanganyar from June to December 2021. This study used primary data and secondary data. The data sources of this study were obtained through three sources, namely the principal, teachers, and students. Data collection techniques in this study used interviews, observations and documentation. the validity of the data by using triangulation and data analysis techniques using interactive . the results showed . The form of habituation program planned by Muhammadiyah Darul Arqom Karanganyar High School in supporting character education is through habituation methods in accordance with the vision and mission of the school so that the Realization of the Islamic Generation of Berakhlakul Karimah and Intellectuals. In addition, in the preparation of planning this habituation method, the principal and the curriculum do not run alone. All school parties, including students, teachers, administrative staff and the school quality assurance team participated in the process of making habituation methods so that they would run or be used in schools. Then the principal certifies what has been decided at the time of the meeting to establish such a habituation method. The implementation of the habituation program in supporting character education at Muhammadiyah Darul Arqom Karanganyar High School is by carrying out disciplinary activities carried out by students by entering school before 07.00. doing 5 S both inside the school environment and outside the school, tadarus, the implementation of infaq which is carried out in each class by collecting sincere money which is carried out every Friday, congregational dhuhur prayers, extracurricular activities and carrying out annual habituation, namely like the ramdhan activities. The form of evaluation of character education through habituation at Muhammadiyah Darul Arqom Karanganyar High School Evaluation of the implementation of character education through habituation is carried out by the principal, school committee and teachers using data on activity reports, activity schedules, as well as by looking at the accountability of the implementing officer, as well as accountability for the use of finances in financing activities. The results of the evaluation of the implementation of the character education program through habituation at Muhammadiyah Darul Arqom Karanganyar High School for the 2020/2021 school year have been broadly achieved and can run optimally.